2020
DOI: 10.3389/fonc.2020.598970
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Unique Case of Pediatric Central Nervous System Embryonal Tumor Harboring the CIC–LEUTX Fusion, Germline NBN Variant and Somatic TSC2 Mutation: Expanding the Spectrum of CIC-Rearranged Neoplasia

Abstract: Central nervous system (CNS) embryonal tumors (WHO grade IV) are a heterogeneous group of rare, poorly differentiated neuroepithelial malignant neoplasms that commonly occur in children, and they have a poor prognosis. The 2016 WHO (World Health Organization) classification of CNS tumors created a major shift in paradigm of the classification of embryonal tumors. However, some cases were still difficult to classify. Further integrative genomic analysis is needed to improve the precise classification, diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“…Therefore, only a few case series describing its imaging features exist. 6,7,[10][11][12][13] In our international cohort of 25 patients, we found that these were supratentorial, often large, multilobulated tumors with little-orno perifocal edema. Tumors nearly always showed a mix of solid and cystic/necrotic components.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, only a few case series describing its imaging features exist. 6,7,[10][11][12][13] In our international cohort of 25 patients, we found that these were supratentorial, often large, multilobulated tumors with little-orno perifocal edema. Tumors nearly always showed a mix of solid and cystic/necrotic components.…”
Section: Discussionmentioning
confidence: 72%
“…The other article was a case of an embryonal tumor of the central nervous system in a child. This case not only had the CIC‐LEUTX fusion gene but also had NBN germline mutations and TSC2 lineage mutations 18 . So far, there are only three reports on CIC‐LEUTX fusion tumors, with a total of four cases, and this case is the fifth case (Table 2).…”
Section: Discussionmentioning
confidence: 88%
“…LEUTX gene is expressed almost exclusively during embryonal life and plays an important role in embryonal genome activation through its N‐terminal highly conserved homeodomain (HD), which is responsible for promoter binding and consequent transcription of target genes 12,13 . LEUTX rearrangements with CIC and KAT6A as fusion partners have been described in CNS tumors and acute myeloid leukaemia, respectively 14‐16 . Recent studies have suggested that CIC‐LEUTX fusion may work similarly to CIC‐DUX4 , as both LEUTX and DUX4 contain HD domains, which may confer chimeric transcriptional regulatory properties to CIC, likely enhancing its transcriptional activity 17‐19 …”
Section: Discussionmentioning
confidence: 99%
“…12,13 LEUTX rearrangements with CIC and KAT6A as fusion partners have been described in CNS tumors and acute myeloid leukaemia, respectively. [14][15][16] Recent studies have suggested that CIC-LEUTX fusion may work similarly to CIC-DUX4, as both LEUTX and DUX4 contain HD domains, which may confer chimeric transcriptional regulatory properties to CIC, likely enhancing its transcriptional activity. [17][18][19] BRD4 is a regulator of gene transcription, DNA replication and repair, and has been involved in numerous forms of human cancers, for example, BRD4-NUT driven NUT midline carcinoma, and its role as therapeutic target has been recently investigated.…”
Section: Discussionmentioning
confidence: 99%